Tourist Experience as a Driver of Satisfaction at Kampung Batik Orang Kranggan (OKRA) Surabaya - Abidan Zulfan Fanani; Yudiana Indriastuti (Jurnal Toursci, 2026)
Background. Kampung Batik Orang Kranggan (OKRA) Surabaya is a community-based cultural tourism destination that integrates batik-making education with the creative economy. Aims. This study aims to identify and analyze the influence of tourist experience on tourist satisfaction at Kampung Batik Orang Kranggan (OKRA) Surabaya. Methods. The study used a quantitative method with an explanatory approach. The sample was determined using the Slovin formula with a purposive sampling technique, obtaining 87 respondents from a population of 683 tourists in 2025. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression with the help of SPSS 25. Result. The results show that tourist experience has a positive and significant effect on tourist satisfaction, with the regression equation Y = 1.489 + 0.641X, a t-count value of 7.709 > t-table 1.988 (Sig. 0.000 < 0.05), and a coefficient of determination (R²) of 0.411, meaning that tourist experience contributes 41.1% to tourist satisfaction. Conclusion. These findings confirm the importance of managing educational and interactive tourism experiences in improving tourist satisfaction at community-based cultural tourism destinations.